Neural activation during risky decision-making in youth at high risk for substance use disorders. Issue 2 (30th August 2015) - Hulvershorn, Leslie A.; Hummer, Tom A.; Fukunaga, Rena; Leibenluft, Ellen; Finn, Peter; Cyders, Melissa A.; Anand, Amit; Overhage, Lauren; Dir, Allyson; Brown, Joshua
Abstract: Risky decision-making, particularly in the context of reward-seeking behavior, is strongly associated with the presence of substance use disorders (SUDs). However, there has been little research on the neural substrates underlying reward-related decision-making in drug-naïve youth who are at elevated risk for SUDs. Participants comprised 23 high-risk (HR) youth with a well-established SUD risk phenotype and 27 low-risk healthy comparison (HC) youth, aged 10–14. Participants completed the balloon analog risk task (BART), a task designed to examine risky decision-making, during functional magnetic resonance imaging. The HR group had faster reaction times, but otherwise showed no behavioral differences from the HC group. HR youth experienced greater activation when processing outcome, as the chances of balloon explosion increased, relative to HC youth, in ventromedial prefrontal cortex (vmPFC). As explosion probability increased, group-by-condition interactions in the ventral striatum/anterior cingulate and the anterior insula showed increasing activation in HR youth, specifically on trials when explosions occurred. Thus, atypical activation increased with increasing risk of negative outcome (i.e., balloon explosion) in a cortico-striatal network in the HR group. These findings identify candidate neurobiological markers of addiction risk in youth at high familial and phenotypic risk for SUDs. Highlights: Neural response to outcomes of risky-decisions appears to be a more sensitive endophenotypic target than making choices in high risk preadolescents. Atypically increased activation in a region associated with risky decision making, was found prior to the use of drugs of abuse. Striatal activation abnormalities suggest a failure to learn from adverse consequences.